2013
DOI: 10.1186/1472-6947-13-56
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid seasonal prediction model for tuberculosis incidence in China

Abstract: BackgroundTuberculosis (TB) is a serious public health issue in developing countries. Early prediction of TB epidemic is very important for its control and intervention. We aimed to develop an appropriate model for predicting TB epidemics and analyze its seasonality in China.MethodsData of monthly TB incidence cases from January 2005 to December 2011 were obtained from the Ministry of Health, China. A seasonal autoregressive integrated moving average (SARIMA) model and a hybrid model which combined the SARIMA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 13 publications
3
61
0
Order By: Relevance
“…However, few hybrid prediction models have been used to predict TB incidence in China. Shiyi Cao, et al [31] constructed a SARIMA-GRNN model with the data of national TB reported cases from Jan 2005 to Dec 2011. Because the ability of reporting TB cases is different in various places and the magnitude and pattern of TB vary with regions in China.…”
Section: Discussionmentioning
confidence: 99%
“…However, few hybrid prediction models have been used to predict TB incidence in China. Shiyi Cao, et al [31] constructed a SARIMA-GRNN model with the data of national TB reported cases from Jan 2005 to Dec 2011. Because the ability of reporting TB cases is different in various places and the magnitude and pattern of TB vary with regions in China.…”
Section: Discussionmentioning
confidence: 99%
“…The ARIMA model includes autoregressive (AR) model, moving average (MA) model, and seasonal autoregressive integrated moving average (SARIMA) model [2]. The Augmented Dickey-Fuller (ADF) [3] unit-root test helps in estimating whether the time series is stationary. Log transformation and differences are the preferred approaches to stabilize the time series [4].…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…One of these methods is the Increased Dickey-Fuller (ADF) unit root test. 8 Log transformation and differences are the preferred approaches to stationary the time series. 9 Seasonal and nonseasonal differences were used to stationary the term trend and periodicity.…”
Section: Methodsmentioning
confidence: 99%